An open-source platform for 3D-printed redox flow battery test cells. Issue 6 (21st February 2022) - O'Connor, Hugh; Bailey, Josh J.; Istrate, Oana M.; Klusener, Peter A. A.; Watson, Rob; Glover, Stephen; Iacoviello, Francesco; Brett, Dan J. L.; Shearing, Paul R.; Nockemann, Peter
Abstract : A framework for improving cell design and providing researchers with low-cost, open-source, 3D-printed redox flow battery test cells. Abstract : The development of new, large-scale stationary energy storage technologies, such as redox flow batteries, is vital to fully utilise renewable energy resources. However, test cells capable of assisting in this development can be prohibitively expensive and unreliable. Here, an open-source, low-cost, customisable 3D-printed test cell is presented as an alternative. These newly developed cells are designed to be printable using affordable desktop 3D-printers and readily available polymers. A simulation-led design optimisation yielded an improved internal manifold geometry that demonstrated improved real-world performance. The polymers used have been tested for chemical compatibility and through the use of advanced X-ray micro-CT, optimised parameters for 3D-printing have been identified. This framework provides a straightforward process enabling researchers to produce robust cells at an extremely low cost, helping to democratise research and widen accessibility to flow electrochemistry.